Sex distribution in children with tympanosclerosis after insertion of a tympanostomy tube - (:unkn) unknown (SPRINGER-VERLAG, 2001)
Tympanostomy tube insertion is an accepted treatment for otitis media with effusion in children. Several clinical studies have shown that tubs insertion may cause myringosclerosis. During the period 1988 to 1997 we treated 533 ears from 311 children who had otitis media with effusion by inserting tympanostomy tubes. Most of these (431 ears from 251 children) were re-examined in 1998 and sex and occurrence of myringosclerosis at the tube insertion site were noted. Myringosclerosis was observed in 31% of ears of girls treated with tubes, a helens in boys 71% of ears showed myringosclerosis. This difference between sexes may indicate a genetic predisposition such as that seen in atherosclerosis.
Keywords: tympanosclerosis; atherosclerosis; tympanostomy; genetic predisposition; SECRETORY OTITIS-MEDIA; GROMMET INSERTION; FOLLOW-UP; T-TUBES; MYRINGOTOMY